2020
DOI: 10.3390/molecules25020275
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Reduction Potential in Anaerobic Digestion of Organic Fraction of Municipal Solid Waste and Food Waste

Abstract: Anaerobic digestion (AD) is a commonly used method of processing waste. Regardless of the type of the used digestate (fertilizer, feedstock in case of solid-state fermentation, raw-material in case of thermal treatment) effective pathogen risk elimination, even in the case of high pathogen concentration is essential. An investigation of the survival time and inactivation rate of the Salmonella Senftenberg W775, Enterococcus spp., and Ascaris suum eggs during thermophilic anaerobic digestion performed on labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The infectious properties of HE can be preserved between 20 months and 6 yr [41]. In this study, D1 reported a higher level of HE than D2 (60% reduction) and D3 (total inactivation).…”
Section: Resultsmentioning
confidence: 50%
“…The infectious properties of HE can be preserved between 20 months and 6 yr [41]. In this study, D1 reported a higher level of HE than D2 (60% reduction) and D3 (total inactivation).…”
Section: Resultsmentioning
confidence: 50%
“…These requirements were applied in the EU regulation of fertilizers. The AD in thermophilic conditions ensures the proper sanitization of OFMSW [14].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be stated that waste biological treatment can bring environmental gains. AD brings more benefits than single composting, mainly due to the possibility of energy recovery from waste [33], despite the digestate and its proper sanitization [14]. Some researchers have confirmed the soil amendment effect of a digestate [17,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations